A morpho-histological and ultrastructural study of the mandibular glands of Atta sexdens worker ants (Hymenoptera : Formicidae) - Pavon, L. F.; Mathias, Maria Izabel Camargo [UNESP] (California State University, 2001)
We describe here the morphology, histology and ultrastructure of the mandibular glands of Atta sexdens (Hymenoptera: Formicidae) worker ants. The mandibular glands consist of a reservoir with an excretory duct and a secretory portion linked to the reservoir trough canaliculi. These glands have the same morphology in the three castes studied, differing only in size, with smaller glands observed in minima workers and larger glands in soldiers.
Keywords: Hymenoptera; Formicidae; ants; mandibular gland; morphology; histology; ultrastructure